Categories:
Mathematics .
Convolution theorem
The convolution theorem states that a convolution in the real domain
is equal to a product in the frequency domain.
This fact is especially useful for computation,
as it allows replacing an O ( n 2 ) \mathcal{O}(n^2) O ( n 2 ) convolution
with an O ( n log ( n ) ) \mathcal{O}(n \log(n)) O ( n log ( n )) transform and product.
The convolution theorem is usually expressed as follows,
where F ^ \hat{\mathcal{F}} F ^ is the Fourier transform ,
and A A A and B B B are the constants from its definition:
A ( f ∗ g ) ( x ) = F ^ − 1 { f ~ ( k ) g ~ ( k ) } B ( f ~ ∗ g ~ ) ( k ) = F ^ { f ( x ) g ( x ) } \begin{aligned}
\boxed{
\begin{aligned}
A \: (f * g)(x)
&= \hat{\mathcal{F}}{}^{-1}\Big\{ \tilde{f}(k) \: \tilde{g}(k) \Big\}
\\
B \: (\tilde{f} * \tilde{g})(k)
&= \hat{\mathcal{F}}\Big\{ f(x) \: g(x) \Big\}
\end{aligned}
}
\end{aligned} A ( f ∗ g ) ( x ) B ( f ~ ∗ g ~ ) ( k ) = F ^ − 1 { f ~ ( k ) g ~ ( k ) } = F ^ { f ( x ) g ( x ) }
Proof
Proof.
We expand the right-hand side of the theorem and rearrange the integrals:
F ^ − 1 { f ~ ( k ) g ~ ( k ) } = B ∫ − ∞ ∞ f ~ ( k ) ( A ∫ − ∞ ∞ g ( x ′ ) e i s k x ′ d x ′ ) e − i s k x d k = A ∫ − ∞ ∞ g ( x ′ ) ( B ∫ − ∞ ∞ f ~ ( k ) e − i s k ( x − x ′ ) d k ) d x ′ = A ∫ − ∞ ∞ g ( x ′ ) f ( x − x ′ ) d x ′ = A ( f ∗ g ) ( x ) \begin{aligned}
\hat{\mathcal{F}}{}^{-1}\Big\{ \tilde{f}(k) \: \tilde{g}(k) \Big\}
&= B \int_{-\infty}^\infty \tilde{f}(k) \bigg( A \int_{-\infty}^\infty g(x') \: e^{i s k x'} \dd{x'} \bigg) e^{-i s k x} \dd{k}
\\
&= A \int_{-\infty}^\infty g(x') \bigg( B \int_{-\infty}^\infty \tilde{f}(k) \: e^{-i s k (x - x')} \dd{k} \bigg) \dd{x'}
\\
&= A \int_{-\infty}^\infty g(x') \: f(x - x') \dd{x'}
\\
&= A \: (f * g)(x)
\end{aligned} F ^ − 1 { f ~ ( k ) g ~ ( k ) } = B ∫ − ∞ ∞ f ~ ( k ) ( A ∫ − ∞ ∞ g ( x ′ ) e i s k x ′ d x ′ ) e − i s k x d k = A ∫ − ∞ ∞ g ( x ′ ) ( B ∫ − ∞ ∞ f ~ ( k ) e − i s k ( x − x ′ ) d k ) d x ′ = A ∫ − ∞ ∞ g ( x ′ ) f ( x − x ′ ) d x ′ = A ( f ∗ g ) ( x )
Then we do the same again,
this time starting from a product in the x x x -domain:
F ^ { f ( x ) g ( x ) } = A ∫ − ∞ ∞ f ( x ) ( B ∫ − ∞ ∞ g ~ ( k ′ ) e − i s x k ′ d k ′ ) e i s k x d x = B ∫ − ∞ ∞ g ~ ( k ′ ) ( A ∫ − ∞ ∞ f ( x ) e i s x ( k − k ′ ) d x ) d k ′ = B ∫ − ∞ ∞ g ~ ( k ′ ) f ~ ( k − k ′ ) d k ′ = B ( f ~ ∗ g ~ ) ( k ) \begin{aligned}
\hat{\mathcal{F}}\Big\{ f(x) \: g(x) \Big\}
&= A \int_{-\infty}^\infty f(x) \bigg( B \int_{-\infty}^\infty \tilde{g}(k') \: e^{-i s x k'} \dd{k'} \bigg) e^{i s k x} \dd{x}
\\
&= B \int_{-\infty}^\infty \tilde{g}(k') \bigg( A \int_{-\infty}^\infty f(x) \: e^{i s x (k - k')} \dd{x} \bigg) \dd{k'}
\\
&= B \int_{-\infty}^\infty \tilde{g}(k') \: \tilde{f}(k - k') \dd{k'}
\\
&= B \: (\tilde{f} * \tilde{g})(k)
\end{aligned} F ^ { f ( x ) g ( x ) } = A ∫ − ∞ ∞ f ( x ) ( B ∫ − ∞ ∞ g ~ ( k ′ ) e − i s x k ′ d k ′ ) e i s k x d x = B ∫ − ∞ ∞ g ~ ( k ′ ) ( A ∫ − ∞ ∞ f ( x ) e i s x ( k − k ′ ) d x ) d k ′ = B ∫ − ∞ ∞ g ~ ( k ′ ) f ~ ( k − k ′ ) d k ′ = B ( f ~ ∗ g ~ ) ( k )
For functions f ( t ) f(t) f ( t ) and g ( t ) g(t) g ( t ) that are only defined for t ≥ 0 t \ge 0 t ≥ 0 ,
the convolution theorem can also be stated using
the Laplace transform :
( f ∗ g ) ( t ) = L ^ − 1 { f ~ ( s ) g ~ ( s ) } \begin{aligned}
\boxed{
(f * g)(t)
= \hat{\mathcal{L}}{}^{-1}\Big\{ \tilde{f}(s) \: \tilde{g}(s) \Big\}
}
\end{aligned} ( f ∗ g ) ( t ) = L ^ − 1 { f ~ ( s ) g ~ ( s ) }
Because the inverse Laplace transform L ^ − 1 \hat{\mathcal{L}}{}^{-1} L ^ − 1 is usually difficult,
the theorem is often stated using the forward transform instead:
L ^ { ( f ∗ g ) ( t ) } = f ~ ( s ) g ~ ( s ) \begin{aligned}
\boxed{
\hat{\mathcal{L}}\Big\{ (f * g)(t) \Big\}
= \tilde{f}(s) \: \tilde{g}(s)
}
\end{aligned} L ^ { ( f ∗ g ) ( t ) } = f ~ ( s ) g ~ ( s )
Proof
Proof.
We expand the left-hand side.
Note that the lower integration limit is 0 instead of − ∞ -\infty − ∞ ,
because we choose to set both f ( t ) f(t) f ( t ) and g ( t ) g(t) g ( t ) to zero for t < 0 t < 0 t < 0 :
L ^ { ( f ∗ g ) ( t ) } = ∫ 0 ∞ ( ∫ 0 ∞ g ( t ′ ) f ( t − t ′ ) d t ′ ) e − s t d t = ∫ 0 ∞ ( ∫ 0 ∞ f ( t − t ′ ) e − s t d t ) g ( t ′ ) d t ′ \begin{aligned}
\hat{\mathcal{L}}\Big\{ (f * g)(t) \Big\}
&= \int_0^\infty \bigg( \int_0^\infty g(t') \: f(t - t') \dd{t'} \bigg) e^{-s t} \dd{t}
\\
&= \int_0^\infty \bigg( \int_0^\infty f(t - t') \: e^{-s t} \dd{t} \bigg) \: g(t') \dd{t'}
\end{aligned} L ^ { ( f ∗ g ) ( t ) } = ∫ 0 ∞ ( ∫ 0 ∞ g ( t ′ ) f ( t − t ′ ) d t ′ ) e − s t d t = ∫ 0 ∞ ( ∫ 0 ∞ f ( t − t ′ ) e − s t d t ) g ( t ′ ) d t ′
Then we define a new integration variable τ = t − t ′ \tau = t - t' τ = t − t ′ , yielding:
L ^ { ( f ∗ g ) ( t ) } = ∫ 0 ∞ ( ∫ 0 ∞ f ( τ ) e − s ( τ + t ′ ) d τ ) g ( t ′ ) d t ′ = ∫ 0 ∞ ( ∫ 0 ∞ f ( τ ) e − s τ d τ ) g ( t ′ ) e − s t ′ d t ′ = ∫ 0 ∞ f ~ ( s ) g ( t ′ ) e − s t ′ d t ′ = f ~ ( s ) g ~ ( s ) \begin{aligned}
\hat{\mathcal{L}}\Big\{ (f * g)(t) \Big\}
&= \int_0^\infty \bigg( \int_0^\infty f(\tau) \: e^{-s (\tau + t')} \dd{\tau} \bigg) \: g(t') \dd{t'}
\\
&= \int_0^\infty \bigg( \int_0^\infty f(\tau) \: e^{-s \tau} \dd{\tau} \bigg) \: g(t') \: e^{-s t'} \dd{t'}
\\
&= \int_0^\infty \tilde{f}(s) \: g(t') \: e^{-s t'} \dd{t'}
\\
&= \tilde{f}(s) \: \tilde{g}(s)
\end{aligned} L ^ { ( f ∗ g ) ( t ) } = ∫ 0 ∞ ( ∫ 0 ∞ f ( τ ) e − s ( τ + t ′ ) d τ ) g ( t ′ ) d t ′ = ∫ 0 ∞ ( ∫ 0 ∞ f ( τ ) e − s τ d τ ) g ( t ′ ) e − s t ′ d t ′ = ∫ 0 ∞ f ~ ( s ) g ( t ′ ) e − s t ′ d t ′ = f ~ ( s ) g ~ ( s )
References
O. Bang,
Applied mathematics for physicists: lecture notes , 2019,
unpublished.